Spatial structure increases the benefits of antibiotic production in Streptomyces. (26th August 2019) - Westhoff, Sanne; Otto, Simon B.; Swinkels, Aram; Bode, Bo; van Wezel, Gilles P.; Rozen, Daniel E.
Abstract: Bacteria in the soil compete for limited resources. One of the ways they might do this is by producing antibiotics, but the metabolic costs of antibiotics and their low concentrations have caused uncertainty about the ecological role of these products for the bacteria that produce them. Here, we examine the benefits of streptomycin production by the filamentous bacterium Streptomyces griseus . We first provide evidence that streptomycin production enables S. griseus to kill and invade the susceptible species, S. coelicolor, but not a streptomycin‐resistant mutant of this species. Next, we show that the benefits of streptomycin production are density dependent, because production scales positively with cell number, and frequency dependent, with a threshold of invasion of S. griseus at around 1%. Finally, using serial transfer experiments where spatial structure is either maintained or destroyed, we show that spatial structure reduces the threshold frequency of invasion by more than 100‐fold, indicating that antibiotic production can permit invasion from extreme rarity. Our results show that streptomycin is both an offensive and defensive weapon that facilitates invasion into occupied habitats and also protects against invasion by competitors. They also indicate that the benefits of antibiotic production rely on ecological interactions occurring at small local scales.